BUZOQDAGI RAXIT KASALLIK TARIXI, BELGILARI VA DAVOLASH: https://doi.org/10.5281/zenodo.14219984 - Rejepbayev , J.E.; Farmonov , N.O.; Zoytova, S.A (International scientific and practical conference, 2024)
The article presents the essence of the disease of calves with hypovitaminosis D, the causes of the violation of these processes, as well as the main methods of examination for the diagnosis of diseases with hypovitaminosis D and a preliminary analysis of the literature.